Митне оформлення вантажів в умовах цифровізації: проблеми та перспективи - Сисоліна, І. П.; Кононенко, Л. В.; Сисоліна Н. П.; Sysolina, I.; Kononenko, L.; Sysolina, N. (Гельветика, 2024)
Стаття присвячена проблемам митного оформлення вантажів, визначенню його сучасного стану та перспектив розвитку в умовах цифровізації. Зазначено, що актуальність дослідження митного оформлення вантажів сьогодні пов’язано із світовими процесами глобалізації та цифрорізації. Акцентовано увагу на тому, що митне оформлення зазвичай було і залишається складною процедурою, яка потребує ґрунтовних знань щодо правильності подання відомостей з метою завершення митного оформлення відповідно до митних режимів переміщення товарів через митний кордон України. Зазначено, що в Україні експорт продукції агропромислового комплексу, є однією з основних статей доходу України вже протягом багатьох років. З’ясовано, що сьогодні здебільшого цифровізація таможених процедур зводиться до заміни фізичної документації (паперової) звичайних торговельних процедур електронними (безпаперовими), які створюються з використанням цифрових технологій, тобто оцифровки. Запропоновано з метою оптимізації процедури митного оформлення вантажів при впровадженні та використанні цифрових технологій враховувати інноваційні зміни. Обґрунтовано, що використання переваг інноваційних змін цифровізації дозволить оптимізувати процедури митного оформлення вантажів, зокрема сільськогосподарської техніки. The article is devoted to the problems of customs clearance of goods, determination of its current state and prospects for development in the context of digitalization. It is noted that the relevance of the study of customs clearance of goods today is associated with the global processes of globalization and digitalization. An integral part of globalization processes is international trade, the landscape of which is currently undergoing significant changes in the context of digitalization. Accordingly, customs is also undergoing transformation. The authors emphasizes that customs clearance has usually been and remains a complex procedure requiring thorough knowledge of the correctness of information to complete customs clearance in accordance with the customs regimes for moving goods across the customs border of Ukraine, and today this procedure is complicated by the increase in international trade. The purpose of the article is to study the impact of digitalization on the customs clearance procedure, to outline the problematic issues and to determine the development prospects. It is noted that in Ukraine, exports of agricultural products have been one of the main sources of income for Ukraine for many years. It is emphasized that the implementation of IT solutions at customs requires a sufficient number of qualified personnel with the appropriate level of digital competencies, as well as technology development specialists, whose main activities should be to monitor the development of innovations, their feasibility for implementation, develop relevant projects and attract investment for their implementation. It is found that today, for the most part, the digitalization of customs procedures is reduced to the replacement of physical documentation (paper) of conventional trade procedures with electronic (paperless) ones created using digital technologies, i.e. digitization. It is proposed that in order to optimize the customs clearance procedure, innovative changes should be taken into account when introducing and using digital technologies. It is substantiated that taking advantage of innovative changes in digitalization will allow optimizing the procedures for customs clearance of goods, in particular, agricultural machinery. The practical value of these proposals is to reduce risks and optimize the customs clearance procedure.
Customs clearance of goods in the context of digitalization: problems and prospects
Keywords: сільськогосподарська техніка; митне оформлення; митні процедури; міжнародна торгівля; ризики; agricultural machinery; customs clearance; customs procedures; international trade; risks